Somatic mutations associate with clonal expansion of CD8+ T cells - Lundgren, Sofie; Myllymäki, Mikko; Järvinen, Timo; Keränen, Mikko A. I.; Theodoropoulos, Jason; Smolander, Johannes; Kim, Daehong; Salmenniemi, Urpu; Walldin, Gunilla; Savola, Paula; Kelkka, Tiina; Rajala, Hanna; et al. (American Association for the Advancement of Science, 2025)
Somatic mutations in T cells can cause cancer but also have implications for immunological diseases and cell therapies. The mutation spectrum in nonmalignant T cells is unclear. Here, we examined somatic mutations in CD4+ and CD8+ T cells from 90 patients with hematological and immunological disorders and used T cell receptor (TCR) and single-cell sequencing to link mutations with T cell expansions and phenotypes. CD8+ cells had a higher mutation burden than CD4+ cells. Notably, the biggest variant allele frequency (VAF) of non-synonymous variants was higher than synonymous variants in CD8+ T cells, indicating non-random occurrence. The non-synonymous VAF in CD8+ T cells strongly correlated with the TCR frequency, but not age. We identified mutations in pathways essential for T cell function and often affected lymphoid neoplasia. Single-cell sequencing revealed cytotoxic TEMRA phenotypes of mutated T cells. Our findings suggest that somatic mutations contribute to CD8+ T cell expansions without malignant transformation.